ILRI: New livestock research institute with a global mandate - Fitzhugh, H.A. (World Association for Animal Production, 1995)
The International Livestock Research Institute (ILRI) is a new institute within the Consultative Group on International Agricultural Research (CGIAR) born of a long-felt need to integrate and globalize the CGIAR livestock research resources. Having inherited the assets and programs of the two former CGIAR livestock centres--the International Laboratory for Research on Animal Diseases (ILRAD), in Kenya, and the International Livestock Centre for Africa (ILCA), in Ethiopia, ILRI is directly responsible for about two-thirds of all CGIAR livestock and livestock-related research in developing regions. The institute has been established to provide leadership in research on major problems of animal production and health in developing regions and to be a world centre for scientific knowledge on international agricultural research centres (IARCs), national agricultural research systems (NARS) and advanced research institutes (ARIs). The paper highlights and discusses the establishment of ILRI and its mandate, first-year Developments, global agenda for livestock research, system wide livestock initiative, ILRI core programs and programme implementation.